2022
DOI: 10.3389/fbioe.2022.844011
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Photothermal Analysis Induced by MoS2 Nanoparticles by Raman Spectroscopy

Abstract: Two-dimensional nanomaterials, such as MoS2 nanosheets, have been attracting increasing attention in cancer diagnosis and treatment, thanks to their peculiar physical and chemical properties. Although the mechanisms which regulate the interaction between these nanomaterials and cells are not yet completely understood, many studies have proved their efficient use in the photothermal treatment of cancer, and the response to MoS2 nanosheets at the single-cell level is less investigated. Clearly, this information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…UV–vis DRS spectra were recorded only for the oxide-supported samples because carbon-supported samples are black. In bulk MoS 2 , direct electronic transitions between the conduction band and valence band result in two absorption peaks around 610 and 670 nm. , For the MoS 2 catalysts supported on alumina, silica, and titania, the UV–vis peaks of MoS 2 were observed and easily distinguished from those of the corresponding supports even in air. In our spectra, beside the absorption bands of supports, several broad peaks centered around 420, 470, and 570 nm were observed, but no bands were present above 600 nm (Figure S3). This difference might be explained by the ultradispersion of MoS x species, leading to the modification of their electronic properties, or due to the partial oxidation of MoS 2 nanoclusters in air .…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…UV–vis DRS spectra were recorded only for the oxide-supported samples because carbon-supported samples are black. In bulk MoS 2 , direct electronic transitions between the conduction band and valence band result in two absorption peaks around 610 and 670 nm. , For the MoS 2 catalysts supported on alumina, silica, and titania, the UV–vis peaks of MoS 2 were observed and easily distinguished from those of the corresponding supports even in air. In our spectra, beside the absorption bands of supports, several broad peaks centered around 420, 470, and 570 nm were observed, but no bands were present above 600 nm (Figure S3). This difference might be explained by the ultradispersion of MoS x species, leading to the modification of their electronic properties, or due to the partial oxidation of MoS 2 nanoclusters in air .…”
Section: Resultsmentioning
confidence: 58%
“…In bulk MoS 2 , direct electronic transitions between the conduction band and valence band result in two absorption peaks around 610 and 670 nm. 50,51 For the MoS 2 catalysts supported on alumina, silica, and titania, the UV−vis peaks of MoS 2 were observed and easily distinguished from those of the corresponding supports even in air. 52−55 In our spectra, beside the absorption bands of supports, several broad peaks centered around 420, 470, and 570 nm were observed, but no bands were present above 600 nm (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…This also means that the final dispersion will contain 2D NSs of varied thicknesses, which can be separated in accordance with their size and thickness upon liquid cascade centrifugation. In this context, the acquisition of UV–Vis spectra is a quick approach to evaluate the average number of layers <N>, average size <L> and average concentration <C> for the exfoliated dispersion [ 38 , 39 , 40 , 41 ]. Indeed, within one sample/dispersion, UV spectra show characteristic, size-dependent spectral changes originating mostly from the absorbance and scattering components of the extinction, as the optical extinction spectra of small and large nanosheets include contributions from both the edge and basal plane effects, respectively [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bulk MoS 2 exhibits high hydrophobicity and, upon exfoliation, the contact angle of the bulk material decreases; after further centrifugation steps, the angle is reduced further and the material will transform from a hydrophobic material to a hydrophilic material in a given solvent [ 71 ]. Normally, when exfoliated in pure water, MoS 2 and WS 2 NSs exhibit surface charges in the range of −26 mV to −32 mV, which provides a stable dispersion and sufficient electrostatic repulsive forces to avoid the aggregation of dispersed 2D TMDs [ 38 , 41 , 68 ]. Interestingly, we found that the ς-potential values were significantly more negative in cyrene than those obtained with water for both materials, WS 2 being significantly more negative than MoS 2 with values of −86.5 ± 1.5 and −50 ± 3, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation